This kind of trouble : a novel - Eze, Tochi (Tiny Reparations Books, Penguin Random House, 2025)
"Benjamin Fletcher was good at surviving. He'd survived cancer at forty-seven, a motor bike accident at fifty-nine, a heart attack at sixty-one. Now, at sixty-seven, it seemed like the only demand life threw at him was to survive the consequences of the past. When Benjamin lands in 1960s Nigeria, hoping to explore his roots after the death of his half-Nigerian father, he falls in love with Margaret. As the two learn more about their respective histories, they realize their lineage is interwoven in the deepest of ways-their ancestors had met decades earlier, with tragic results. Unfolding over three distinct timelines spanning a century, This Kind of Trouble reveals the unsettling events that took place in a small Nigerian village in 1905 - the same events that will eventually tear Margaret and Benjamin apart 60 years later. When we meet them again in 2005, they have been estranged for decades, content to leave the heartbreaks of the past behind them. But when their grandson begins to show signs of what Margaret believes is the mental instability that has troubled her family for generations as a kind of curse, she decides the family must come together and confront the generational traumas that have shaped her and Benjamin both, and to reckon with transgressions both intimate and ancestral. Beautifully written, transporting, narratively ambitious, and featuring an unusual forbidden love story, This Kind of Trouble asks us to consider the ways we are all beholden to the past, and what we owe the future. With this debut novel, Tochi Eze announces herself as a major new literary voice in world literature"-- Provided by publisher.